SAFE SURGERY: IMPORTANT CONDUCTS - Mesquita Gomes, Renata; da Silva Cardoso, Lidiane; Alencar de Medeiros Pereira, Márcia; Ribeiro da Silva, Magdala; Claudino do Nascimento, Nathalia; Feitosa Rodrigues, Lutigard; Alexandre Judeikis, Guilherme; de Lima Ferreira, Mateus; Carolina Salustino dos Santos, Maria (Health and Society, 2022)
Safe surgery procedures ensure patient safety, as established by the Ministry of Health. The research was built by reading articles, books and bibliography in a group. The checking process has important results for the patient’s life, formalizing the entire surgery and offering greater possibilities of care and fewer failures.